Pengembangan Smartphone Gateway Sebagai Perantara Pengiriman Data Lahan Menuju Data Center - Fadhlan Muhammad; Adhitya Bhawiyuga; Reza Andria Siregar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Recently, Development of Internet of Things techology becomes very popular. Internet of Things is a network that connect everything with communication protocol. There are various implementations of Internet of Things. The implementation of Agriculture Internet of Things was one of them. But, in some Agriculture scenarios does not provide network infrastructure. Also, Agriculture technology development affected by the field space. In that case Agriculture Internet of Things need to developed with mobility. Smartphone gateway could be implemented to develop a system with mobility. Development of Smartphone gateway need system design, protocol communication, data transformation mechanism, data storage. To solve this problem, this research develop gateway as data communication agent with Bluetooth low energy for gateway-sensor communication and Intenet for gateway-cloud communication. Gateway also have a feature to capture an image from the Smartphone device as data source. As the result of this research gateway-sensor communication have success ratio of 92% with data send rate of 33.6 Byte/s for a sensor and Gateway-cloud communication have 100% data send without data loss. Smarthphone device capable to store data depends on the remaining internal memory space with data growth rate under 1KB for every 100 sensor data and 3.067MB for every image.